Processo de renovação do auto de vistoria do corpo de bombeiros - Veronez, Denise [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
This work deals with the stages of the process of renewal of a Notice of Inspection of Fire Department (AVCB) set of structural measures, technical and organizational integrated to ensure the building an optimum level of protection in the security segment fire and panic according to the laws of fire safety standards. The work presented all the literature about the process, their justifications to force deploy in a company to fire safety, the benefits that this standard offers, the facilities in a company that has a AVCB and the great importance in society, presents some examples where there contained the fire safety regulations and their unhappy outcomes, difficulties encountered, examples of how to proceed, step by step and the lesson that this process requires great care, dedication, professionals with the required knowledge and severity to completion

Neste trabalho são abordadas as etapas do processo de renovação de um Auto de Vistoria do Corpo de Bombeiros (AVCB), conjunto de medidas estruturais, técnicas e organizacionais integradas para garantir a edificação um nível ótimo de proteção no segmento de segurança contra incêndios e pânico de acordo com as legislações das normas de segurança contra incêndio. O trabalho apresenta toda a literatura sobre o processo, suas justificativas para obrigar a implantar em uma empresa a segurança contra incêndio, os benefícios que essa norma oferece, as facilidades numa empresa que apresenta um AVCB e a grande importância na sociedade, retrata exemplos onde não continham as normas de segurança contra incêndio e seus desfechos infelizes, as dificuldades encontradas, exemplos de como proceder, passo a passo e a lição de que esse processo exige muito cuidado, dedicação, profissionais habilitados e severidade até sua conclusão
Keywords: Bombeiros; Edificios - Incêndios e prevenção de incêndio; Construção civil - Especificações; Fire fighters